ANALYZING THE EFFECTS OF BIOLOGICALLY ACTIVE COMPOUNDS ASKOLIT, ASXAQ, AND ANTI-ULCER ON STOMACH AND INTESTINAL TRACT ULCERS (British Journal of Global Ecology and Sustainable Development, 2025)
The article discusses about how effect ASKOLIT, ANTI-ULCER and ASXAQ for ulcerative colitis and peptic ulcer disease the distribution areas of the plants, as well as the unsurpassed role of leaves in promoting human health, the chemical composition and biological significance of vitamins ASKOLIT, ANTI-ULCER and ASXAQ, as well as several recommendations for the treatment of ulcerative colitis modern medicine. ASKOLIT, ANTI-ULCER and ASXAQ did not have any adverse toxic effects. traditional medicine based on the compound leaves plants, as well as data on the mechanism of action on the colon wall and their discussion.